Hubungan antara emotion focused coping dan kepuasan hidup pada mahasiswa - Eka Nur Maulida Sari (Cognicia, 2019)
Students have responsibilities and roles in college, the adaptation process that occurs, makes students face many problems in achieving their goals and life satisfaction. Late adolescence towards early adulthood makes emotional more dominant in overcoming the problem, so that emotion focused coping has an important role in regulating emotion when face problem to proceed towards solving problems in achieving life satisfaction. This study aims to determine the correlation between emotion focused coping and students’ life satisfaction. This study designed as correlational quantitative. The subject involved in this study were 650 students. The sampling technique used was proportionate stratisfied random sampling. The data collection instruments used were emotion focused coping scale and life satisfaction scale. The data were analyzed by using product moment correlation. The result of this study indicates that there is a significant correlation between emotion focused coping and life satisfaction (p = 0.000, r = 0.346). The effective contribution of emotion focused coping variables to life satisfaction is 12%.